From flummoxed to focused: A mixed-methods study of preventive practices during the COVID-19 pandemic among intern doctors working in a rural tertiary care hospital of Maharashtra, India - Mandar Baviskar; Anup Kharde; Shubham Gadekar; Shubham Sheth; Akshata Chordiya (Wolters Kluwer Medknow Publications, 2020)
Introduction: Intern doctors are important in the functioning of a teaching hospital. Their health and sanitation practices can, therefore, influence disease transmission rates. Methods: A simultaneous quantitative + qualitative study was conducted on 110 intern doctors working in a rural tertiary care hospital. Percentage values and Chi-square tests were used to compare responses in male and female interns and triangulation-incorporated qualitative inputs. Results: Overall, the practices were sound, but lapses in the protocol were reported, especially in areas with higher patient footfall. Females were more likely to follow proper hand hygiene (P = 0.042), use alcohol based sanitizer and keep it on their person (P = 0.017), use gloves as instructed (P = 0.02). And males diligently observed social distancing (P = 0.0001), and followed mobile phone hygiene (P = 0.003). Conclusion: Despite the scale of pandemic, interns have tried their best to follow guidelines and commonsense measures. Clear protocols, positive reinforcement, and monitoring can prevent lapses in preventive measures.